Forced convection of nanofluid in double vented cavity system separated by perforated conductive plate under magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Sci Ltd, 2023)
In this study, forced convection in a double vented cavity system separated by a perforated conductive partition plate is studied under magnetic field effects. Nanofluid is used while two phase modeling approach is adopted. The conjugate thermal system is studied for different values of Reynolds number (250-1000), Hartmann number (0-50), and conductivity ratio (0.01-100). Variations of the size and inner part of the conductive plate are also considered while solid volume fraction of nanoparticles is taken as 0.03. Thermal performance improvements are observed by increasing the Reynolds number and conductivity ratio. When nanofluid is used instead of pure fluid, the average Nusselt number (Nu) increment becomes 9% at the lowest and highest Reynolds number cases. When magnetic field is activated, the highest variation in the average Nu is seen for the left upper part while the amount becomes 14%. The Nu increments become 240% for the left upper part when lowest and highest conductivity cases are compared while this amount is 18% when all hot walls are considered. When full partition and perforated plate partitions are compared, less than 1.5% in the variation of thermal performance is achieved while 29.6% reduction in the volume of the partition is seen. Using perforated partitions is recommended as it results in the reduction of the material, cost and weight of the overall thermo-fluid system.
Keywords: MHD flow; Two phase flow; Nanofluid; Finite element method; Perforates partition; Double vented cavity